Successful therapy of collagen-induced arthritis with TNF receptor-IgG fusion protein and combination with anti-CD4. - Williams, R; Ghrayeb, J; Feldmann, M; Maini, R (1995)
We have previously shown that anti-tumour necrosis factor (TNF) monoclonal antibody (mAb) ameliorates established collagen-induced arthritis and that the efficacy of this form of treatment can be enhanced by concurrent anti-CD4 treatment. Here we assess the efficacy of a human p55 TNF receptor-IgG fusion protein (p55-sf2), given alone or with anti-CD4 mAb. TNF receptor-IgG fusion protein (100 micrograms) suppressed paw swelling and limb recruitment in established arthritis and reduced the incidence of erosions in the proximal interphalangeal joints from 92% to 50%, which was comparable to 41% erosions using anti-TNF mAb. Methylprednisolone acetate (4.2 mg/kg/week) reduced clinical signs of inflammation in a manner comparable to TNF blockade but had little effect on the incidence of erosions. Co-administration of anti-CD4 and TNF receptor-IgG led to an even greater therapeutic effect than TNF receptor-IgG alone, with the incidence of erosions being reduced from 100% to 17%. Serological analyses showed that the beneficial effects of anti-CD4 and TNF receptor-IgG could be partly explained by the ability of anti-CD4 to prevent a neutralizing antibody response. These results confirm the importance of TNF in destructive inflammatory arthritis and demonstrate the feasibility of therapeutically targeting TNF with a form of TNF receptor. Finally, the findings confirm the beneficial effects of TNF-targeted therapy coupled with anti-CD4 therapy.